Legal Counseling: Preventing Crime through a Local Wisdom Approach: Penyuluhan Hukum: Mencegah Kejahatan melalui Pendekatan Kearifan Lokal - Salam, Safrin; Suhartono, Rizki Mustika; Karim, La Ode Muhammad; Yusran, Yusran; Azhar, Eko (Indonesian Journal of Law and Economics Review, 2023)
This scientific article aims to explore the role of local wisdom in strengthening law enforcement and preventing crime in Buton community. By employing a research methodology adhering to academic standards, the study identifies the forms of local wisdom and its implications for crime prevention. The research findings highlight the significance of cultural festivals, particularly the "pesta kampung" tradition, which embodies values such as communal harmony, compassion, and mutual cooperation. These values contribute to raising legal awareness and fostering a sense of responsibility among the community. The results underscore the potential of local wisdom approaches as effective tools for crime prevention. The implications of this study can inform policymakers, legal practitioners, and researchers worldwide, shedding light on the importance of incorporating local cultural practices into legal frameworks to promote law-abiding behaviors and enhance community well-being. Highlights: Local wisdom plays a vital role in preventing crime through community engagement. Cultural festivals serve as platforms to reinforce law enforcement values and promote legal awareness. Incorporating local wisdom into crime prevention strategies can enhance community well-being and foster a sense of responsibility among individuals. Keywords: Crime prevention, local wisdom, cultural festivals, law enforcement, community engagement.